Pengomposan Sampah Organik Sebagai Upaya Pengelolaan Lingkungan di Sekolah Dasar - Sophia Shanti Meilani; Muamar Rasman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
School is one of waste generation source other than residential. Appropriate school waste management shall be conducted to avoid health problems and environmental pollution. Composting is one of the method in organic waste treatment. Organic waste from Tanah Tinggi Elementary School, Tangerang was composted in composter drum. Raw organic waste was mixed with manure with ratio 2:1, 3:1, and 3:2. Temperature increase during composting and end result composition were observed. Through composting process, the temperature increased from 33-35oC to 40-41oC. Temperature increase implied microorganism activity in decomposing organic waste. Compost product quality indicated the best C/N ratio was resulted from organic waste which waste mixed with manure in 3:1 ratio. Organic waste composting at school will reduce the quantity of waste which shall be transported to final disposal site. Another benefit is to improve awareness in environmental protection. School roles in composting program consist of providing location for composting and disseminating information about the benefit of organic waste composting.